Safety and effectiveness of parent- or nurse-controlled analgesia in neonates: a systematic review. Issue 1 (12th January 2022) - Muirhead, Renee; Kynoch, Kathryn; Peacock, Ann; Lewis, PA
ABSTRACT: Objective: The aim of this systematic review was to determine the safety and effectiveness of parent- or nurse-controlled analgesia on neonatal patient outcomes. More specifically, the objective was to determine the effect of parent- or nurse-controlled analgesia on neonatal pain scores, analgesic use, and incidence of iatrogenic withdrawal syndrome, as well as any opioid-associated adverse events Introduction: Despite recent innovations in neonatology leading to significant improvements in short- and long-term outcomes for newborns requiring intensive care, optimal management of pain and distress remains a challenge for the multidisciplinary treatment team. The inability of neonates to communicate pain easily, inconsistent practice among health professionals, insufficient analgesic prescriptions, and delays in medical reviews all impact effective pain management. Exploring the effect of parent- or nurse-controlled analgesia may identify a modality that negates these concerns and improves the pharmacological management of pain in newborns. Inclusion criteria: This review considered experimental and observational studies evaluating the safety and effectiveness of parent- or nurse-controlled analgesia that included babies born at 23 weeks' gestation to four weeks post-term. The interventions considered for inclusion were any type of analgesia delivered by an infusion pump that allowed bolus dosing or a continuous analgesic infusion with bolus dosing as required. Studies using algorithms and protocols to guide timing and dosage were eligible for inclusion. Comparators included the standard management of pain for neonates in the newborn intensive care unit. A modification to the a priori protocol was made to include all neonates nursed outside of a neonatal intensive care unit to ensure all studies that examined the use of parent- or nurse-controlled analgesia in the neonatal population were included in the review. Methods: An extensive search of six major databases was conducted (CINAHL, Cochrane Library, Embase, PubMed, PsycINFO, and Web of Science). Studies published from 1997 to 2020 in English were considered for inclusion in this review. Databases searched for unpublished studies included MedNar and ProQuest Dissertations and Theses. Results: Fourteen studies were included in this review: two randomized controlled trials, six quasi-experimental studies, one case-control study, and five case series. There was considerable heterogeneity in the interventions and study outcome measures within the studies, resulting in an inability to statistically pool results. The small sample sizes and inability to distinguish data specific to neonates in six of the studies resulted in low quality of evidence for the safety and effectiveness of parent- or nurse-controlled analgesia in neonates. However, studies reporting neonatal data demonstrated low pain scores and a trend in reduced opioid consumption when parent- or nurse-controlled analgesia was used. Conclusions: The use of parent- or nurse-controlled analgesia in the neonatal population has shown some effect in reducing the amount of opioid analgesia required without compromising pain relief or increasing the risk of adverse events. Due to the paucity of evidence available, certainty of the results is compromised; therefore, larger trials exploring the use of parent- or nurse-controlled analgesia in neonates and the development of nurse-led models for analgesia delivery are needed. Systematic review registration number: PROSPERO CRD42018114382